The Influence of Capital Adequacy Ratio (CAR), Non performing Loans (NPL), Operating Costs To Operating Income (BOPO) on Liquidity as Measured by Loan to Deposit Ratio at Bank Negara Indonesia Tbk - Elwardi Hasibuan; Siti Ummi Arfah Nasution; Sayyaditina Aisyah (ProBisnis : Jurnal Manajemen, 2021)
The purpose of this research is to analyze and test the effect of CAR, NPL, BOPO on the LDR of PT. Bank BNI Indonesia Tbk. This type of research is explanatory research. The sample used in this research is PT. Bank BNI Indonesia Tbk, which published its financial statements for the period 2006-2013. Data collection techniques are library research and field research. This study uses multiple linear regression for data analysis with the help of the Eviews 6 program. The results of the analysis test show that the CAR and BOPO ratios have no effect on the LDR ratio, while the NPL ratio has a significant effect on the LDR ratio.